1995
DOI: 10.1039/c39950002453
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced effects of ring tilting on the intramolecular electron-transfer rate in mixed-valence polyalkyl-substituted biferrocenium cations

Abstract: The results of X-Ray structural determinations, electrochemical measurements, near-IR, 57Fe Mossbauer measurements, and an explanation of the influence of steric factors o n the electron-transfer rates for a series of polyalkyl substituted mixed-valence biferrocenium triiodides are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…There are numerous studies on other bridged biferrocene systems (e.g., Fc-Fc, , Fc-S-Fc, Fc-PR-Fc, Fc-CR 2 -Fc, , and Fc-C 2 R 4 -Fc 34,39 ) for which two redox couples are generally observed by cyclic voltammetry. The number of electrochemical investigations on isolated bridged oligo(ferrocenes) decreases rapidly with an increasing number of linked ferrocene units present.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous studies on other bridged biferrocene systems (e.g., Fc-Fc, , Fc-S-Fc, Fc-PR-Fc, Fc-CR 2 -Fc, , and Fc-C 2 R 4 -Fc 34,39 ) for which two redox couples are generally observed by cyclic voltammetry. The number of electrochemical investigations on isolated bridged oligo(ferrocenes) decreases rapidly with an increasing number of linked ferrocene units present.…”
Section: Resultsmentioning
confidence: 99%
“…Binuclear transition metal complexes in which the metal atoms are in close enough proximity to permit through space or bridging ligand-mediated interactions have been well-studied. This is particularly the case for biferrocenes which yield mixed-valent monocations (e.g., 1 and 2 ) , that possess delocalization on a variety of different time scales depending on subtle structural factors and even solid state environmental effects. , Recently, oligomeric metallocene-based species have attracted attention with respect to their electrochemical, electronic, and magnetic properties.
…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, compound 11 has a valence-trapped electronic structure at temperatures below 150 K and becomes a valence-detrapped electronic structure at a temperature of ∼200 K. In comparison with para-substituted compounds ( 10 − 12 ), a valence-detrapped electronic structure is seen even at 77 K for ortho-substituted mixed-valence compounds of 13 and 14 . We suggested that relatively minor perturbations caused by interactions between neighboring cations and anions have pronounced effects on electron transfer. ,
1
…”
Section: Introductionmentioning
confidence: 93%
“…The mixed-valence states of conjugated ferrocene dimers have attracted considerable attention for decades because they are valuable examples affording intrinsic information regarding intramolecular electron-exchange reactions. It has been shown that the chemical structure of the conjugated spacer group and its length dramatically affect the electronic interaction between the ferrocene units. Solvation effects on the electron exchange rate are also significant, and those for biferrocene and Fc−C⋮C−Fc have been analyzed by Powers and Meyer, by Blackbourn and Hupp, and by Weaver and co-workers 13 based on the Marcus−Hush theory .…”
Section: Introductionmentioning
confidence: 99%